From Patañjali to the “Gospel of Sweat”: Yoga’s Remarkable Transformation from a Sacred Movement into a Thriving Global Market - Munir, Kamal; Ansari, Shahzad (Shaz); Brown, Deborah (Administrative Science Quarterly, 2021)
Movements seeking to infuse markets with moral values often end up utilizing the market mechanism and support from mainstream actors to scale up, even if it comes at the cost of diluting their founding ethos. But this process can be particularly challenging for movements that are explicitly opposed to using a market mechanism as a means of scaling up. Our analysis of yoga between 1975 and 2016 reveals how a countercultural movement fundamentally opposed to a capitalist market economy but seeking to grow can paradoxically become syncretic with or infiltrated by concepts and beliefs that are core to the market system but incompatible with the movement’s original ethos. We show how, before such a movement can be commodified, it must be de-essentialized, a process that requires stripping away key aspects of its history, context, and religious commitments and transforming collective goals into individual ones. This process involves not only external entrepreneurs looking to mine the movement but also movement leaders seeking wider enrollment of resource-rich actors to scale the movement up. We show how codes borrowed from parallel movements and templates borrowed from markets can be instrumental in driving such a movement’s transformation. Through this extreme case of the yoga movement, we advance understandings of how movements can become syncretic with values and practices they fundamentally oppose.